Orthosurgical management of a patient with cleft lip and palate - Sergio Martires; Nandini V Kamat; Vikas Dhupar (Wolters Kluwer Medknow Publications, 2020)
A 31-year-old male patient reported with a chief complaint of a forwardly placed lower jaw. Oral examination revealed Angle's Class III relationship bilaterally and cephalometrically; the patient presented with a small-sized retrognathic maxilla and normal mandible. Orthosurgical treatment was carried out with 4 mm of maxillary advancement and 4 mm of mandibular setback to achieve ideal overjet, overbite, and intercuspation of teeth. The ANB angle showed a drastic change from −9.5° to 1° and a successful conversion of the skeletal profile from Class III to Class I. Orthosurgical treatment can thus be an effective means of treating a patient with cleft lip and palate but requires a detailed understanding of the case and a sound diagnosis to attain a successful outcome.